Hematological and Blood Chemistry values in a semi-free population of white-nosed coatis (Nasua narica) in La Venta Tabasco, Mexico - Rovirosa-Hernández, María de Jesús; García-Orduña, Francisco; Morales-Mávil, Jorge E.; Hernández-Salazar, Laura Teresa; Hermida-Lagunes, Javier; Lagunes-Merino, Omar; Fuentes-Anaya, Tlaoli (Instituto de Ecología, A.C., 2012)
Clinical analyses of Procyonidae groups are extremely limited. The aim of this work was to obtain gender baseline data on the blood chemistry and hematological values of Nasua narica, in conditions of semi-freedom. For this, 14 males adults and 30 females adults were sedated with ketamine hydrochloride and captured. The blood was collected from the femoral artery, and conventional techniques were used to analyze the samples. Males showed statistical differences in hemoglobin, hematocrit and erythrocytes, compared to females. The females on the other hand having higher platelet counts than the males. For blood chemistry, the females showed higher concentrations of magnesium compared with the males. On the other hand, the males showed higher values in Albumin/Globulin relation with respect to the females. These results could be useful as reference values for adult individuals of Nasua narica, in order to develop future criteria regarding the health-disease processes of this species.